Peningkatan Hasil Belajar Materi Sisi Bangun Datar Melalui Model CPS Berbasis Media Smart Box - Trisna Dewi Moerti; Siti Masfuah; Nur Hadi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The purpose of this study was to improve learning outcomes on the material of flat shapes with sides through the Creative Problem Solving (CPS) model based on Smart Box media for third grade students of SD 1 Sadang. The subjects in this study were 17 third grade students. The research method used was Classroom Action Research (CAR) consisting of two cycles, each cycle carried out for two meetings. Data collection techniques included interviews, observations, and tests. The results showed an increase in student learning outcomes in the cognitive domain. Learning completeness before the action (pre-cycle) only reached 29.41%, increased to 58.80% in cycle I, and increased again to 76.5% in cycle II. Based on the results of the study, it can be concluded that the application of the CPS model based on Smart Box media is effective in improving students' cognitive learning outcomes on the material of flat shapes with sides in third grade students of SD 1 Sadang.